Cell Receptor-Basement Membrane Interactions in Health and Disease: a Kidney-Centric View - Borza, Corina M. (Curr Top Membr, 2015)
Cell-extracellular matrix (ECM) interactions are essential for tissue development, homeostasis, and response to injury. Basement membranes (BMs) are specialized ECMs that separate epithelial or endothelial cells from stromal components and interact with cells via cellular receptors, including integrins and discoidin domain receptors. Disruption of cell-BM interactions due to either injury or genetic defects in either the ECM components or cellular receptors often lead to irreversible tissue injury and loss of organ function. Animal models that lack specific BM components or receptors either globally or in selective tissues have been used to help with our understanding of the molecular mechanisms whereby cell-BM interactions regulate organ function in physiological and pathological conditions. We review recently published work on animal models that explore how cell-BM interactions regulate kidney homeostasis in both health and disease.